Assessing Zoonotic Bacterial Pathogens: Risks and Public Health Implications from Livestock in Residential Areas of Mosul: Menilai Patogen Bakteri Zoonosis: Risiko dan Implikasi Kesehatan Masyarakat dari Ternak di Daerah Pemukiman di Mosul - Huda Jihad G. Al-shattrawi (Universitas Muhammadiyah Sidoarjo, 2024)
Despite the increasing frequency of cattle in residential areas, particularly in residential neighbourhoods, little is known about the potential health hazards associated with their presence. This cross-sectional investigation examined the incidence of zoonotic agents in 108 cattle samples collected from various locations around Mosul city. The standardized medical examination and livestock owner interviews occurred from October 4 to December 18, 2024. We identified bacterial pathogens in samples from each animal's pharynx, nose, ear, mouth, and faeces. We determined that all of the cattle were in excellent health. Out of 108 cattle, 84 (or 78% of the total) tested positive for zoonotic agents. The principal pathogen was ESBL Escherichia coli (E. coli) isolated from 51 (60.7%) faecal samples. We isolated extended-spectrum beta-lactamase C. difficil organisms from 16 cows (19%). We isolated MRSA from 12 (14.3%), VRE from 3 (3.6%), and Salmonella spp. from 2 (2.4%) of the cows. ESBL E. coli showed significant resistance, particularly to amoxicillin (86.3%) and gentamicin (78.4%). Clostridium difficile exhibited complete resistance to amoxicillin (100%), while MRSA demonstrated full resistance to several antibiotics, including gentamicin and vancomycin. VRE and Salmonella spp. also displayed high resistance rates. Highlights: Zoonotic Agents in Cattle: 78% tested positive in residential areas. Pathogen Resistance: ESBL E. coli, MRSA, and others showed high resistance. Health Hazards: Antibiotic-resistant bacteria pose significant public health risks. Keywords: Zoonotic, bacterial pathogens, public health, cattle, multi-drug resistant